25 Years of Contrast-Enhanced MRI: Developments, Current Challenges and Future Perspectives. Issue 1 (January 2016) - Lohrke, Jessica; Frenzel, Thomas; Endrikat, Jan; Alves, Filipe; Grist, Thomas; Law, Meng; Lee, Jeong; Leiner, Tim; Li, Kun-Cheng; Nikolaou, Konstantin; Prince, Martin; Schild, Hans; et al.
Abstract In 1988, the first contrast agent specifically designed for magnetic resonance imaging (MRI), gadopentetate dimeglumine (Magnevist® ), became available for clinical use. Since then, a plethora of studies have investigated the potential of MRI contrast agents for diagnostic imaging across the body, including the central nervous system, heart and circulation, breast, lungs, the gastrointestinal, genitourinary, musculoskeletal and lymphatic systems, and even the skin. Today, after 25 years of contrast-enhanced (CE-) MRI in clinical practice, the utility of this diagnostic imaging modality has expanded beyond initial expectations to become an essential tool for disease diagnosis and management worldwide. CE-MRI continues to evolve, with new techniques, advanced technologies, and novel contrast agents bringing exciting opportunities for more sensitive, targeted imaging and improved patient management, along with associated clinical challenges. This review aims to provide an overview on the history of MRI and contrast media development, to highlight certain key advances in the clinical development of CE-MRI, to outline current technical trends and clinical challenges, and to suggest some important future perspectives. Funding Bayer HealthCare.